Microgel particles, microgel film adhesive prepared from microgel particles, preparation method and application of microgel film adhesive
By preparing fully physically crosslinked microgel particles, the shortcomings of amphoteric polymer gels in terms of adhesion and compliance are solved, and the firm bonding and good compliance of microgel films on various substrates are achieved. , has broad application prospects.
Patent Information
- Application Number
- CN202510031178.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing amphoteric polymer gels have insufficient adhesion and compliance, resulting in poor adhesion to different substrate surfaces and insufficient structural design flexibility.
By preparing fully physically crosslinked microgel particles prepared from polyzwitterionic ions and acrylic acid as raw materials, the acrylic monomer is fully dispersed in the polyzwitterionic long chain by reverse phase emulsion method, forming rich chain entanglements and supramoleculars to enhance adhesion strength to the substrate surface.
The excellent mechanical properties and adhesion properties of the microgel film are achieved, allowing it to form a strong adhesive with strong compliance to the substrate surface on a variety of different substrates, and have good self-healing and ductile properties. .
Smart Images

Figure CN119409894A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to microgel particles and a microgel film adhesive prepared therefrom, a preparation method and application thereof. Background Art
[0002] Generally speaking, the bonding strength of polymer adhesives is closely related to two factors: adhesion and cohesion. Adhesion refers to the force between the adhesive and the surface on which it is bonded, while cohesion refers to the interaction within the polymer network. Adhesive failure is usually caused by cohesive failure due to the destruction of the interaction between the adhesive and the surface on which it is bonded or poor mechanical stability. In addition, in order to achieve strong bonding performance, the adhesive is also required to have good compliance with the surface on which it is bonded, to quickly adapt to the microstructure of the surface on which it is bonded, and to increase the contact area.
[0003] From the perspective of adhesion, to bond an adhesive to another material, it is often necessary to utilize the chemical or physical properties of the polymer network. The former is bonded by chemical bonding, which requires the adhesive or adherend to have specific chemical groups, has certain usage restrictions, and once the chemical bond is broken, the adhesion will fail. The latter is bonded by physical topological entanglement, which requires the adherend to have a porous microstructure, and is only applicable to porous adherends such as hydrogels and living tissues, and its scope of application is still limited.
[0004] From the perspective of cohesion, in recent years, many studies have been devoted to solving the problem of cohesive failure caused by weak mechanical properties, and the following strategies have been explored: constructing a double network, increasing the crosslinking density, using multifunctional crosslinkers, and introducing anisotropic structures. However, these strategies mainly focus on enhancing interactions (covalent or non-covalent) to dissipate energy, which may lead to strong morphological stability of the adhesive itself and poor compliance with different substrate surfaces, which is not conducive to increasing the contact area with the substrate and improving the bonding strength.
[0005] In recent years, among a variety of different adhesives, hydrogel adhesives have been widely used in various biomedical fields such as tissue sealing and soft robotics. Compared with traditional adhesives synthesized from petroleum-based materials, bio-based gel adhesives, especially hydrogels, have greater practical advantages due to their environmental friendliness and good degradability. However, hydrogels are composed of sparse polymer networks and a large amount of water. Water is often the main obstacle to hydrogel adhesion. Water molecules in hydrogels may hinder the close contact between the polymer network and the adhesion surface. Even if a layer of water molecules is tightly bound to the adhesion surface, the binding force cannot be transmitted to the adjacent water molecules and polymer network. For example, zwitterionic polymers contain both cations and anions in the same unit. Zwitterions have excellent hydration ability due to hydrogen bonding and electrostatic interactions and are one of the most common raw materials for preparing bio-based hydrogels. However, although zwitterionic hydrogels can be designed to exhibit high strength and toughness, they have poor adhesion to the substrate surface because the hydration film is easily formed at the interface due to their strong hydration ability. However, some studies have found that when the charge balance of zwitterionic polymers is broken, it is difficult to form a dense hydration layer on its surface, which means that the groups on the polymer chain can fully contact the polar groups on the surface of the adherend, increasing the interaction between molecules and generating adhesion. However, existing studies often prepare bulk gels, which require the introduction of crosslinking agents to improve the mechanical strength of the gels. In addition, the initiator directly induces chemical crosslinking to form gels, which may cause uneven polymerization, resulting in poor mechanical properties of the gels and reduced adhesion. This type of gel structure design is not flexible enough and has insufficient compliance to the substrate.
[0006] Therefore, there is an urgent need to provide a new strategy to further improve the adhesion of amphoteric polymer gels and their compliance to different substrate surfaces in order to broaden their application range. Summary of the invention
[0007] The purpose of the present invention is to provide a completely physically cross-linked microgel particle prepared from polyzwitterion and acrylic acid, wherein the acrylic acid monomer is fully dispersed in the long chain of the polyzwitterion for polymerization by a reverse emulsion method, thereby forming abundant chain entanglements and supramolecular effects (dihydrogen bonds and electrostatic interactions), and acrylic acid as an anionic monomer can break the ionic balance of the zwitterion polymer chain and change the dipole-dipole interaction between the zwitterion polymer chains, thereby mediating the electrostatic interaction to enhance the adhesion strength to the substrate surface.
[0008] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows: The invention provides a microgel particle, which is prepared from polyzwitterions and acrylic acid as raw materials; the particle size of the microgel particle is 10nm-100nm; the mass ratio of the polyzwitterions to the acrylic acid is 1:(0.5-5).
[0009] Furthermore, the polyzwitterion is a mixture of any one or more of the following: polysulfonated betaine, poly 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium-3-yl)propane-1-sulfonate, polysulfonated betaine acrylamide, poly 1-propylsulfonic acid-3-vinylimidazole inner salt, poly 2-methacryloyloxyethyl phosphorylcholine; preferably polysulfonated betaine.
[0010] Furthermore, the mass ratio of the polyzwitterion to acrylic acid is 1:3.5.
[0011] Furthermore, the microgel particles are prepared by dissolving the raw materials and initiator in an aqueous solvent to form a water phase, and then reacting with the oil phase through inverse emulsion polymerization under the action of an emulsifier; The initiator is selected from any one or more of the following: ammonium persulfate, potassium persulfate, sodium persulfate; The aqueous solvent is a 0.05M to 0.15M salt solution; preferably a 0.1M salt solution; The emulsifier is a nonionic emulsifier; The oil phase is selected from any one of the following: liquid paraffin, olive oil, peanut oil, silicone oil, and aromatic hydrocarbons.
[0012] Furthermore, the initiator is ammonium persulfate; the salt solution is lithium chloride solution; the emulsifier is a mixture of Span-80 and Tween-80; and the oil phase is liquid paraffin.
[0013] The present invention also provides a method for preparing the above-mentioned microgel particles, comprising the following steps: (1) uniformly mixing the emulsifier and the oil phase to obtain a mixture; (2) After the raw materials and initiator are dissolved in an aqueous solvent, they are added to the mixture and reacted at 45-55° C. for 3.5-4.5 hours, preferably at 50° C. for 4 hours under anaerobic conditions.
[0014] The present invention also provides a microgel film, which is prepared from the following raw materials in parts by weight: 1 part of the above-mentioned microgel particles and 0-2 parts of a plasticizer.
[0015] Furthermore, the microgel film is prepared by dissolving the microgel particles and a plasticizer in water to form a suspension, which is then poured into a mold and the water is evaporated; the mass fraction of the microgel particles in the suspension is 1% to 1.5%.
[0016] The present invention also provides the use of the above-mentioned microgel particles or microgel films in preparing adhesives.
[0017] Beneficial effects of the present invention: The microgel particles of the present invention are prepared by a new strategy of reverse emulsion polymerization, and the particle size distribution is uniform. No additional crosslinking agent is required, and the particles are completely formed by physical crosslinking. The interaction between individual particles is the collective effect of the short-range force of the primary electrostatic interaction, the van der Waals force and the hydrogen bond. The collective short-range forces of multiple particles accumulated by these physical interactions enable the microgel film to obtain excellent mechanical properties and adhesion properties. Further, the microgel film is prepared by microgel, and the morphology of the microgel will be retained during the film formation process, and the morphology of rough particles will be formed on the surface of the microgel film, further increasing the area between the film and the substrate surface, and enhancing the adhesion; at the same time, a plasticizer can be introduced in the process of preparing the microgel film, and the flexibility of the microgel film can be adjusted by adjusting the amount of plasticizer, so that the design is more flexible. In addition, the complete physical crosslinking interaction gives the hydrogel good self-healing and ductility properties, so the hydrogel can form a strong adhesive with strong compliance to the substrate surface on a variety of different substrates, and can be reused, with broad application prospects.
[0018] Description of terms in this invention: 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium-3-yl)propane-1-sulfonate is a structurally improved sulfonate betaine monomer: 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium-3-yl)propane-1-sulfonate (VBIPS).
[0019] Sulfobetaine acrylamide (SBAA): 1-Propanaminium, N, N-dimethyl-N-[3-[(2-methyl-1-oxo-2-propen-1-yl)amino]propyl]-3-sulfo-, innersalt, CAS number: 5205-95-8.
[0020] 1-Propanesulfonate-3-vinyl imidazolioate: 3-(1-Vinyl-3-imidazolio)-propanesulfonate (VIPS), CAS No.: 46348-09-8.
[0021] 2-Methacryloyloxyethylphosphorylcholine (MPC): 2-Methacryloyloxyethylphosphorylcholine, CAS No.: 67881-98-5.
[0022] Salt solution: a homogeneous system formed by dissolving an inorganic salt or an organic salt in a solvent, including but not limited to lithium chloride, sodium chloride, potassium chloride, PBS and other salt solutions.
[0023] Drying film formation: refers to evaporating the water content of the hydrogel precursor suspension to obtain a solid-state hydrogel film with a water content of not less than 5%.
[0024] Polyzwitterions are polymers formed by the polymerization of zwitterionic monomers; zwitterionic monomers are a class of neutral compounds that carry both positive and negative charges on the same molecule. This compound has oppositely charged groups, that is, there are both positive ions and negative ions in the molecule.
[0025] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0026] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the FT-IR spectra of the microgel particles, sulfobetaine (SBMA) and polyacrylic acid (PAA) of the present invention.
[0028] Figure 2 It is a transmission electron microscope picture of the microgel particles of the present invention.
[0029] Figure 3 The figures are (a) microgel particle suspensions of Examples 1 to 4 of the present invention (concentration 5 wt%), (b) suspensions of microgel PA3 of different concentrations of Example 3 of the present invention, and (c) rheological test result graphs of the microgel PA3 suspension of Example 3 of the present invention (concentration 5 wt%) when the shear rate changes from low to high (up) and from high to low (down).
[0030] Figure 4 5 is a stress-strain curve diagram of the microgel films of Examples 5 to 8 of the present invention.
[0031] Figure 5 3 is a stress-strain curve diagram of the microgel films of Examples 9 to 13 of the present invention.
[0032] Figure 6 The microgel film PA3G of Example 12 of the present invention 1.5 Scanning electron microscope image of .
[0033] Figure 7 3 is a graph showing the test results of the adhesion performance of the microgel films of Examples 9 to 13 of the present invention to the aluminum sheet.
[0034] Figure 8The microgel film PA3G of Example 12 of the present invention 1.5 The adhesion performance test results of different substrates (aluminum sheet, wood, polyethylene, polytetrafluoroethylene, silicone) at different bonding temperatures (25℃, 70℃).
[0035] Fig. 9 The microgel film PA3G of Example 12 of the present invention 1.5 Adhesion strength variation graph after 5 repeated bondings on aluminum sheet and silicone surface. DETAILED DESCRIPTION
[0036] The raw materials and equipment used in the embodiments of the present invention are all known products and can be obtained by purchasing commercially available products. As an example, the polyzwitterion used in the embodiments of the present invention is polysulfonyl betaine (PSBMA), which is synthesized by the following method: Weigh 4g of sulfobetaine (SBMA) and 30ml of deionized water into a round-bottom flask, pass nitrogen for 40min to remove dissolved oxygen in the water, then add 40mg of azobisisobutyramidine hydrochloride (AIBA) and stir at 70ºC for 12h. After the reaction is completed, collect the product, dialyze with distilled water and freeze-dry to obtain the target product PSBMA. The reaction formula is as follows: Example 1. Preparation of microgel particles PA1 of the present invention Weigh 0.6g of Span-80, 0.2g of Tween-80 and 26.43g of liquid paraffin in a three-necked flask and stir them evenly. Dissolve 2.33g of polyzwitterion PSBMA and 1.17g of acrylic acid (AA) in 8.17g of LiCl solution (0.1 M) (the mass ratio of PSBMA and AA is 1:0.5), add APS (1wt% of AA), then dissolve it by ultrasonication, pour it into a constant pressure funnel and adjust the dropping rate to make it slowly drip into the three-necked flask. After the addition is completed, nitrogen is passed through for 20min to deoxygenate, the temperature is raised to 50°C, and the reaction is carried out for 4h. After the reaction is completed, wash with anhydrous ethanol and centrifuge, and repeat three times. The obtained product is dialyzed and freeze-dried with distilled water to finally obtain microgel particles PA1.
[0037] Example 2: Preparation of microgel particles PA2 of the present invention The method was the same as that of Example 1, except that the amount of PSBMA was adjusted to 1.17 g and the amount of AA was adjusted to 2.33 g (the mass ratio of PSBMA to AA was 1:2), to prepare microgel particles PA2.
[0038] Example 3: Preparation of microgel particles PA3 of the present invention The method was the same as that of Example 1, except that the amount of PSBMA was adjusted to 0.78 g and the amount of AA was adjusted to 2.72 g (the mass ratio of PSBMA to AA was 1:3.5), to prepare microgel particles PA3.
[0039] Example 4: Preparation of microgel particles PA4 of the present invention The method was the same as that of Example 1, except that the amount of PSBMA was adjusted to 0.58 g and the amount of AA was adjusted to 2.92 g (the mass ratio of PSBMA to AA was 1:5), to prepare microgel particles PA4.
[0040] Example 5: Preparation of microgel film PA1 of the present invention The microgel particles PA1 of Example 1 were added with water to form a 1.3 wt % suspension, which was then slowly poured into a mold and dried in an oven at 45° C. to form a film, thereby obtaining a microgel film PA1.
[0041] Example 6: Preparation of microgel film PA2 of the present invention The microgel particles PA2 of Example 2 were added with water to form a 1.3 wt % suspension, which was then slowly poured into a mold and dried in an oven at 45° C. to form a film, thereby obtaining a microgel film PA2.
[0042] Example 7: Preparation of microgel film PA3 of the present invention The microgel particles PA3 of Example 3 were added with water to form a 1.3 wt % suspension, which was then slowly poured into a mold and dried in an oven at 45° C. to form a film, thereby obtaining a microgel film PA3.
[0043] Example 8: Preparation of microgel film PA4 of the present invention The microgel particles PA4 of Example 4 were added with water to form a 1.3 wt % suspension, which was then slowly poured into a mold and dried in an oven at 45° C. to form a film, thereby obtaining a microgel film PA4.
[0044] Example 9: Preparation of microgel film PA3G0 of the present invention The microgel particles PA3 of Example 3 were added with water to form a 1.35 wt % suspension, which was then slowly poured into a mold and dried in an oven at 45° C. to form a film, thereby obtaining a microgel film PA3G0.
[0045] Example 10: Microgel film PA3G of the present invention 0.5 Preparation The microgel particles PA3 of Example 3 were added with water to form a 1.35 wt% suspension, and then glycerol (the mass of which was 0.5 times that of the microgel particles PA3) was added, and the mixture was mixed by ultrasonication for 20 min, and then slowly poured into a mold, and dried in an oven at 45°C to form a film, thereby obtaining a microgel film PA3G. 0.5 .
[0046] Example 11. Preparation of microgel film PA3G1 of the present invention The microgel particles PA3 of Example 3 were added with water to form a 1.35 wt% suspension, and glycerol (the mass was equal to that of the microgel particles PA3) was added, and mixed by ultrasonication for 20 min. The mixture was then slowly poured into a mold and dried in an oven at 45°C to form a film, thereby obtaining a microgel film PA3G1.
[0047] Example 12: Microgel film PA3G of the present invention 1.5 Preparation The microgel particles PA3 of Example 3 were added with water to form a 1.35 wt% suspension, and then glycerol (1.5 times the mass of the microgel particles PA3) was added, and the mixture was mixed by ultrasonic for 20 min, and then slowly poured into a mold, and dried in an oven at 45°C to form a film, thereby obtaining a microgel film PA3G. 1.5 .
[0048] Example 13: Preparation of microgel film PA3G2 of the present invention The microgel particles PA3 of Example 3 were added with water to form a 1.35 wt% suspension, and glycerol (the mass of which was twice that of the microgel particles PA3) was then added, mixed by ultrasonication for 20 min, and then slowly poured into a mold and dried in an oven at 45°C to form a film, thereby obtaining a microgel film PA3G2.
[0049] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0050] Structural characterization: The microgel particles of Examples 1 to 4 and the control samples polyacrylic acid (PAA) and sulfonyl betaine monomer (SBMA) were tested using FT-IR spectroscopy (Bruker Tensor-27 spectrometer). Each sample was tested at least 3 times and the wavelength was 500-4000 cm −1 The spectrum was tested within the range of
[0051] The morphology and size of the microgel particles of Examples 1 to 4 were observed using a transmission electron microscope (TEM, Talos F200S, FEI, United States): the microgel dilution was dropped on a copper grid and dried, and then stained with a 2% sodium phosphotungstate solution.
[0052] The surface morphology of the microgel films of Examples 9 to 13 and the interface morphology between the microgel films and the substrate as an adhesive were observed using a scanning electron microscope (SEM, 10 KV, Nano 450 from FEI, USA). The samples were gold-sprayed for 90 s.
[0053] Rheological testing: The relationship between the viscosity and shear rate of the microgel suspension was tested at room temperature using a rheometer (Anton Paar) to characterize the presence of abundant hydrogen bonds and chain entanglements in the suspension: a drop of the pre-prepared PA3 suspension of different concentrations and the suspension of Examples 1 to 4 of the same concentration was dropped onto the rheometer plate. -4 ~10 2 s -1 The viscosity of the microgel suspension was measured in a range of shear rates (mPa.s).
[0054] Mechanical properties test: The mechanical properties of the hydrogels of Examples 5 to 13 were tested using a universal testing machine (CMT6104) at room temperature: the hydrogels were cut into rectangular samples with a length of 30 mm, a width of 5 mm, and a thickness of 0.4 mm, and a tensile test was performed at a speed of 100 mm / min, and each sample was tested three times.
[0055] Adhesion performance test: The bonding strength of the microgel film was tested using the shear overlap method on a universal testing machine. Aluminum sheets, wood chips, PE plastics, silicone and other substrates were attached to the top surface of the film with an overlapping area of 25 mm × 25 mm. Dovetail clamps were used to clamp both sides of the adhesive surface, and the adhered samples were dried at 25°C and 70°C for 16 hours respectively. The treated samples were subjected to a uniaxial tensile force (100 mm / min) using a universal testing machine (CMT6104) until they broke, and the force applied to each sample at the failure point was recorded. The calculation formula for lap shear strength (MPa) is: the ratio of the force at the failure point (N) to the lap shear area (mm 2 ).
[0056] Experimental Example 1: Characterization results of microgel particles of the present invention The FT-IR spectra of the microgel particles of the present invention and the control samples PAA and SBMA are as follows: Figure 1 As shown in the figure, it can be seen that PAA has a peak at 1710 cm -1 The absorption peak at is attributed to the polydihydrogen bonds formed between AAs. Compared with PAA and SBMA, the C=O bonds, CN bonds, and S=O bonds in the microgel particles are shifted. This is because compared with single monomers and polymers, the microgel system has abundant hydrogen bonds and electrostatic interactions.
[0057] From the transmission electron microscopy observation of microgel particles ( Figure 2 ) It can be seen that the microgel particles prepared by different raw material ratios of the present invention all present a particle morphology of uniform size, with a particle size range of 10nm~100nm, and an average size within 50nm.
[0058] The viscosity behavior of the microgel suspension was observed by rheometer, and it was found that there was a shear thinning trend. PA3 samples were selected to prepare dispersions of different concentrations to analyze the relationship between viscosity and shear rate. It was found that the higher the concentration, the greater the viscosity. At the same time, the viscosity also differed from low to high and from high to low when the shear rate changed ( Figure 3 ), indicating the existence of chain entanglement and interaction in the system.
[0059] Experimental Example 2: Characterization results of the microgel film of the present invention From the mechanical properties test results of the microgel films of Examples 5 to 8 ( Figure 4 ) It can be seen that with the increase of acrylic acid, the tensile strength of the microgel film first increases and then decreases, and the elongation shows a decreasing trend. Among them, the microgel film PA3 of Example 7 shows the best tensile strength, which is speculated to have more abundant chain entanglements and molecular interactions. Therefore, Examples 9 to 13 of the present invention all introduce plasticizer glycerol into the film based on PA3, and the mechanical properties test results of Examples 9 to 13 ( Figure 5 ) It can be seen that as the amount of glycerol increases, the ductility of the film is better, but when it reaches 200%, the mechanical strength is low and the elongation begins to decrease.
[0060] From the microgel film PA3G of Example 12 1.5 The SEM images show that the front side of the microgel film (the side in contact with the air) has a relatively rough morphology and contains microgel particles embedded in it ( Figure 6 ), this rough particle morphology can increase the contact area between the film and the substrate surface, which is conducive to enhancing the adhesion. The back of the film is relatively smooth. In fact, from the test results of the adhesion performance of aluminum sheets ( Figure 7 ) It can also be seen that PA3G 1.5 It shows better adhesion strength because it has good mechanical properties and excellent surface compliance. At the same time, the soft and rough adhesive can adapt well to the surface morphology of the substrate, increase the adhesion area, and form a more stable adhesion. When different substrates are used for overlap shearing, it is found that PA3G 1.5 They all have excellent adhesion effects, and placing them in a high temperature environment will greatly promote adhesion ( Figure 8 ), this is because, the increase in temperature can promote the movement of long chains and groups inside the adhesive, increase the interaction between the adhesive and the surface of the substrate, and at the same time, the solvent and water in the adhesive will evaporate in small amounts as the temperature rises, and the adhesive will harden in the pores and uneven interfaces of the substrate, so compared to other substrates, it will achieve better results when adhering to wood chips with rough porous morphology. In addition, PA3G 1.5 The bonding strength will not be significantly reduced even after repeated bonding on aluminum and silicone surfaces. Fig. 9 ).
[0061] In summary, the present invention successfully prepares microgel particles that are completely physically cross-linked, and the microgel film prepared thereby has excellent mechanical properties and adhesion properties. It can form a strong adhesive that has strong surface compliance with the substrate on substrates such as aluminum sheets, wood, and polytetrafluoroethylene, and can be reused, with broad application prospects.
Claims
1. A microgel particle, characterized in that: The microgel particles are prepared from polyzwitterions and acrylic acid as raw materials; the particle size of the microgel particles is 10nm~100nm; the mass ratio of the polyzwitterions to acrylic acid is 1:(0.5~5); the polyzwitterions are a mixture of any one or more of the following: polysulfonate betaine, poly 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium-3-yl)propane-1-sulfonate, polysulfonate betaine acrylamide, poly 1-propylsulfonic acid-3-vinylimidazole inner salt, poly 2-methacryloyloxyethyl phosphorylcholine.
2. The microgel particles according to claim 1, characterized in that The polyzwitterion is polysulfonate betaine.
3. The microgel particles according to claim 1, characterized in that The mass ratio of the polyzwitterion to acrylic acid is 1:3.
5.
4. The microgel particles according to any one of claims 1 to 3, characterized in that: The microgel particles are prepared by dissolving the raw materials and the initiator in an aqueous solvent to form a water phase, and then reacting with the oil phase through inverse emulsion polymerization under the action of an emulsifier; The initiator is selected from any one or more of the following: ammonium persulfate, potassium persulfate, sodium persulfate; The aqueous solvent is a 0.05M~0.15M salt solution; The emulsifier is a nonionic emulsifier; The oil phase is selected from any one of the following: liquid paraffin, olive oil, peanut oil, silicone oil, and aromatic hydrocarbons.
5. The microgel particles according to claim 4, characterized in that The initiator is ammonium persulfate; the salt solution is lithium chloride solution; the emulsifier is a mixture of Span-80 and Tween-80; and the oil phase is liquid paraffin.
6. The method for preparing microgel particles according to claim 4, characterized in that: The steps include: (1) uniformly mixing the emulsifier and the oil phase to obtain a mixture; (2) The raw materials and initiator are dissolved in an aqueous solvent, added to the mixture, and reacted at 45-55° C. for 3.5-4.5 hours under anaerobic conditions.
7. A microgel film, characterized in that: The method is prepared from the following raw materials in parts by weight: 1 part of the microgel particles according to any one of claims 1 to 3 and 0 to 2 parts of a plasticizer.
8. The microgel film according to claim 7, characterized in that The microgel particles and the plasticizer are dissolved in water to form a suspension, which is poured into a mold to evaporate the water; the mass fraction of the microgel particles in the suspension is 1% to 1.5%.
9. Use of the microgel particles according to any one of claims 1 to 3, or the microgel film according to claim 7 or 8 in preparing an adhesive.
Citation Information
Patent Citations
Chitosan / zwitter-ion and acrylic acid copolymer double network self-healing hydrogel and preparation method thereof
CN110372885A
Zwitterionic double network hydrogels
CN112805033A
Tissue adhesive as well as preparation method and application thereof
CN116672490A